Portal cavernoma as a cause of hematemesis in a young unmarried female: A case report (Indian Journal of Case Reports, 2020)
Thrombotic incidents are usually uncommon in unusual sites like portal vein and further in the adolescent age group which presents a potential diagnostic dilemma. Chronic non-cirrhotic non-malignant portal vein thrombosis (PVT) can present at any age group, usually as acute upper gastrointestinal (UGI) bleed. Diagnosis depends on imaging modalities involving Doppler, computed tomography (CT), magnetic resonance imaging, and portography. We report the case of a 20-year-old unmarried girl presented with multiple episodes of hematemesis. Ultrasonography abdomen and CT abdomen revealed PVT with portal cavernous transformation of the portal vein. Her prothrombin time and activated partial thromboplastin time were normal. Her connective tissue workup was normal. A diagnosis of PVT secondary to umbilical vein sepsis during infancy was made. Adolescent patients presented with acute hematemesis should not be neglected for some local cause of UGI bleed but should be evaluated for other rare causes like PVT, for early diagnosis and management to reduce feared complications.